The Influence of Electronic Word of Mouth (E-WoM) and Electronic Service Quality on Brand Image and Purchase Intention - Hartati Sukma Ningrum; Siti Nurlalela (PT Inovasi Pratama Internasional, 2026)
Purchase intention an important role in marketing strategies that can be applied by the information technology and transportation industry by providing the best service for consumers to improve the company's brand image formed from e-service quality and electronic word of mouth optimally. The purpose of this study was to measure more specifically e-service quality against brand image and purchase intention. This type of research is quantitative with a purposive sampling technique distributed through a questionnaire to 100 respondents who use application-based food delivery services in Jakarta. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the 5 hypotheses proposed are accepted, E-service quality was found to have a positive effect on brand image, indicating that good digital service quality can strengthen brand perception. Electronic word of mouth also positively influences brand image, meaning that consumer reviews can enhance the positive perception of a brand. Furthermore, brand image positively influences purchase intention, meaning that the better the brand image, the higher the consumers' intention to purchase. Additionally, e-service quality has a positive effect on purchase intention, showing that a good user experience in the application can increase the desire to make a purchase. Lastly, electronic word of mouth also has a positive effect on purchase intention, indicating that positive reviews from other users can encourage consumers' purchasing decisions. This study contributes to the information technology and transportation industries in maintaining and increasing purchase intention by prioritizing consumer complaints to meet their needs. Furthermore, companies should introduce new innovations in every feature provided in food delivery service applications and present accurate and relevant information to fulfill consumer demands.